Clinical Evaluation of the Efficacy of Coronally Advanced Flap in Combination with Platelet-Rich Fibrin Membrane in the Treatment of Miller Class I Gingival Recessions - Alaood, Omar; Alasqah, Mohammed; Alhomodi, Nawaf; Alqahtani, Noorah; Gufran, Khalid; Shafiq, Sami (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Gingival recession has been associated with dentinal hypersensitivity, root caries, and esthetic compromise. Root coverage procedures aim at providing both tangible and intangible benefits to the patients. Various procedures have been tried to obtain root coverage of single-rooted teeth. Miller Classes I and II gingival recessions hold out the best promise for root coverage as there is no interdental bone and soft-tissue loss associated with these recessions. AIM: The objective of the study was to evaluate and compare the effectiveness of coronally advanced flap (CAF) with platelet-rich fibrin (PRF) membrane with CAF + connective tissue graft (CTG) on recession coverage. MATERIALS AND METHODS: A total of 16 patients required recession coverage for a single tooth were divided into two groups. The test group received CAF + PRF while the control group got CAF + CTG. Different parameters were taken preoperatively (amount of recession, width, and thickness of attached gingiva) and repeated for the two groups 2 months after surgery. RESULTS: Comparing the two groups after 2 months from surgery showed that the PRF not only has an effect in the management of recession but also has a greater effect on tissue thickness. CONCLUSION: PRF is a minimum invasive approach and a promising material for root coverage and manipulating the gingival biotype.